An in vitro study evaluating the efficacy of a novel mount with torque control designed to tighten Osstell SmartPegs - Naughton, David (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2022)
Objectives: The aim of this study was to evaluate the effects that different transducer tightening methods have on implant stability quotient (ISQ) values. A secondary aim was to determine the reliability of ISQ measurements from implants of varying connections and geometries, in various bone densities with different transducer tightening methods. Materials and methods: Fifty six implants, comprising 7 different types of implant, were placed in 8 polyurethane blocks representing D1, D2, D3 and D4 bone densities. Resonance frequency analysis (RFA) transducers were attached to each implant in four different ways: hand tightening with gauze, hand tightening with a plastic wrench, hand tightening with a novel mount with inbuilt torque control and tightening to 6 Ncm with a calibrated torque wrench. ISQ measurements were performed using two Osstell devices, from a buccal and mesial direction and repeated by a second operator. An intra-class correlation coefficient (ICC) was calculated to assess the reliability between the two RFA devices, buccal and mesial directions and operator one and two. Linear mixed effects regression was used to determine the effect explanatory variables had on ISQ values. Results: There was a statistically significant difference in ISQ values obtained by hand tightening transducers with gauze compared to the calibrated torque wrench. There was excellent agreement between the two RFA devices (ICC 0.986) and between buccal and mesial measurements (ICC 0.977). For all transducer tightening methods there was excellent inter-operator agreement for D1 and D2 (ICC >0.8), good agreement for D3 (ICC >0.7) but very poor agreement for D4 (ICC 0.04-0.2). Bone density accounted for 36% of the variation in ISQ values, the implant accounted for 11% and the operator for 6%. Conclusions: Transducer tightening method has a statistically significant impact on ISQ values. However, the greatest impact on ISQ values is due to bone density. Furthermore, reliability of RFA is very poor in soft bone.
APPROVED
Keywords: Resonance frequency analysis; Dental implants